Intrinsic Quality Design in The Making of Preparation Herbal Handsanitizer Based on Kasturi Tobacco Leaves Extracts (Nicotiana tabacum L.) - Andi Eko Wiyono; Herlina Herlina; Riski Mulya Setyawati (Agroindustrial Technology Journal, 2021)
Tobacco leaves contain flavonoids which can be used for the manufacture and development of herbal handsanitizer products. The purpose of this study was to assess the quality attributes, determine the characteristics, and formulate a handsanitizer gel herbalfrom tobacco leaf extract. The determination of product quality attributes is determined based on survey results, while the manufacture of products is carried out based on the results of laboratory experiments. The formulations for the addition of CMC-Napreparation gel hand sanitizer F1, F2, F3 were 3 g, 4 g, and 5 g, respectively. The test result data is presented in the form of tables and figures and analyzed descriptively. The assessment of quality attributes is based on the preference and needs of consumers who are answered by 100 respondents. The formulation evaluation of the handsanitizer gel included organoleptic, pH, homogeneity and dispersibility tests. The handsanitizer gel herbal that consumersprefer a herbal gel handsanitizer that was light brown in color, have a soft aroma (fragrance of flowers and fruit), and gave the appearance of not being sticky, soft, or cold when used. The musk tobacco extract used contains antioxidants in the form of flavonoids with levels of 42.50 mg /100g. The best formulations for prototype development were F2 with a pH value of 7.56; homogeneous; and the spreadability is 6.20.